The heron's cry [large type] - Cleeves, Ann (Cleeves, Ann. Two rivers series., 2021)
"North Devon is enjoying a rare hot summer with tourists flocking to its coastline. Detective Matthew Venn is called out to a rural crime scene at the home of a group of artists. What he finds is an elaborately staged murder--Dr. Nigel Yeo has been fatally stabbed with a shard of one of his glassblower daughter's broken vases. Dr. Yeo is a good man, a public servant, beloved by his daughter. Matthew is unnerved, though, to find that she is a close friend of Jonathan, his husband. Matthew soon finds himself treading carefully through the lies that fester at the heart of his community and a case that is dangerously close to home"--Page 4 of cover.